Vertebrate footprints from the Kem Kem beds (Morocco): A novel ichnological approach to faunal reconstruction - Belvedere, Matteo; Jalil, Nour-Eddine; Breda, Anna; Gattolin, Giovanni; Bourget, Hélène; Khaldoune, Fatima; Dyke, Gareth J. (Palaeogeography, palaeoclimatology, palaeoecology, 2013)
The first survey of vertebrate fossil tracks and trackways from the well-known Kem Kem beds of southern Morocco is here presented. The aims are to: (1) discuss the diversity of vertebrate trackmakers represented in two trace-yielding units at three localities, and (2) apply the novel data to ongoing debates about vertebrate ecological associations within the Kem Kem. The majority of the tracks we recorded from the Kem Kem are tridactyl theropod footprints; other dinosaurian track records include those of possible ornithopod dinosaurs, extremely rare as body fossils within Kem Kem collections. Traces of swimming turtles are reported, alongside the first tracks of crocodyliforms and possible pterosaurs to be recorded from the Moroccan Cretaceous (both unsurprising given their abundance as body fossil records in this region). Differences between the collected ichnological sample and faunal reconstructions made on the basis of skeletal evidence are discussed; as trace fossils record the same environment in which the trackmaker lived (i.e. not subject to post-mortem transportation), data of this type arguably provide a more precise palaeoecological sample than the heavily re-worked and usually fragmentary body fossils from the Kem Kem. •Report and analysis of several vertebrate traces in the Cretaceous “Kem Kem beds”•First occurrence of ornithopod, crocodyliform, and pterosaur tracks in the area•Use of trace assemblage for palaeofaunal reconstructions•Differences with the bone fauna as a key for environmental consideration